The effects of Anadara granosa shell-Stichopus hermanni on bFGF expressions and blood vessel counts in the bone defect healing process of Wistar rats - Rima Parwati Sari; Sri Agus Sudjarwo; Retno Pudji Rahayu; Widyasri Prananingrum; Syamsulina Revianti; Hansen Kurniawan; Aisah Faiz Bachmid (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2017)
Background: Bone damage can be caused by various factors with treatment usually involving graft materials being applied to the defective area. Moreover, in the bone defect healing process, blood vessels are also considered to be an important energy source for cell proliferation. One of the angiogenic factors playing an important role in blood vessel formation is basic fibroblast growth factor (bFGF). Furthermore, synthesized hydroxyapatite derived from Anadara granosa (AG) shells constitutes one of the potential materials for use in bone graft. The gold sea cucumber genus Stichopus hermanni (SH) possesses the ability to stimulate endothelial progenitor cells inducing bFGF. Purpose: This study aims to investigate the effects of AG shells and SH on bFGF expressions and blood vessel counts within the bone healing process. Methods: Twenty four male Wistar rats were divided into three groups, namely: a control group (C), a treatment group was administered with blood cockle shell (AG), and a treatment group with blood cockle shell and golden sea cucumber (AG+SH). Defects were made on their femurs measuring half the diameter of a circular, no. 018. bur These rats were subsequently sacrificed on day 7 after surgery. The expressions of bFGF were measured by means of IHC technique, while the number of blood vessels was quantified using HE technique. The resulting data was subjected to statistical analysis using an Anova test followed by an LSD test (p < 0.05). Results: The one-way Anova test results combined with those of an LSD test showed there to be significant differences in bFGF expressions and blood vessel counts between the control group (K) and the treatment group (AG) as well as between the treatment group (AG) and the treatment group (AG+SH). Conclusions: A combination of Anadara granosa shell and Stichopus hermanni can increase the expression of bFGF and the number of blood vessels on day 7 during the bone healing process in Wistar rats.